Fibroblast growth factor in gastroprotection and ulcer healing: interaction with sucralfate. Issue 7 (July 1993) - Konturek, S J; Brzozowski, T; Majka, J; Szlachcic, A; Bielanski, W; Stachura, J; Otto, W
Abstract : The study was designed to determine the gastroprotective and ulcer healing efficacy of basic transforming growth factor (bFGF) and to assess whether this peptide contributes to the action of sucralfate on the rat stomach. Application of human recombinant bFGF (1-100 micrograms/kg/hour subcutaneously) failed to affect the formation of acute gastric lesions induced by 100% ethanol and acidified aspirin but reduced the stress induced by gastric lesions. Sucralfate (100-200 mg/kg given orally) protected gastric mucosa against the ethanol, aspirin, and stress induced acute gastric lesions but the addition of bFGF (100 micrograms/kg subcutaneously or intragastrically) failed to affect sucralfate induced protection against ethanol or aspirin but increased that against stress. Administration of bFGF (3-300 micrograms/kg/day) by an intragastric or an intraperitoneal route or sucralfate (400 mg/kg/day) orally to rats with acetic acid induced gastric ulcers, enhanced the healing rate of these ulcers during seven day treatment in a dose dependent manner. This was accompanied by a pronounced increase in the number of capillaries and myofibroblasts and in DNA synthesis and DNA and RNA concentrations in the granulation tissue in the ulcer area. [125I]bFGF (1 microCi) applied subcutaneously or intragastrically accumulated in two to threefold higher amounts in the ulcer area than in the intact mucosa, particularly in rats treated with sucralfate. Concurrent treatment with indomethacin (2 mg/kg intraperitoneally) delayed ulcer healing and reduced the binding of labelled bFGF to the ulcer area, angiogenesis, and DNA synthesis by sucralfate. Addition of [125I]bFGF to sucralfate at various pHs resulted in the coprecipitation of bFGF by sucralfate in a pH dependent manner from about 10% at pH 7.0 to 90% at pH 1.5. Thus bFGF shows little protective activity and is not essential for gastroprotection afforded by sucralfate but plays an important part in healing of gastric ulcers possibly due to its growth promoting and angiogenic actions.